2024
DOI: 10.1186/s12889-024-17728-2
|View full text |Cite
|
Sign up to set email alerts
|

Individual, family, and environmental correlates of fundamental motor skills among school-aged children: a cross-sectional study in China

Yuxiu He,
Lin Zhou,
Wei Liang
et al.

Abstract: Objective This cross-sectional study examined the socio-ecological factors influencing fundamental motor skills (FMS) in Chinese school-aged children. Methods A total of 1012 parent-child pairs were randomly sampled between March-1st and April-15th, 2022. Based on the socio-ecological model of Children’s FMS, three levels of factors: individual-level (e.g., demographic, physical, psychological, and behavioral characteristics of children), family-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
0
4
0
1
Order By: Relevance
“…This coincides with the results presented by the authors of [ 35 ], in an intervention study to improve motor development, which showed that 93% of the children evaluated had a lower level of motor development than the chronological age. However, there is evidence that indicates that the higher the chronological age, the higher the motor age, a situation that is explained by the fact that as motor performance increases [ 60 ], there is also a greater maturation of the central nervous system [ 58 , 59 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This coincides with the results presented by the authors of [ 35 ], in an intervention study to improve motor development, which showed that 93% of the children evaluated had a lower level of motor development than the chronological age. However, there is evidence that indicates that the higher the chronological age, the higher the motor age, a situation that is explained by the fact that as motor performance increases [ 60 ], there is also a greater maturation of the central nervous system [ 58 , 59 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Es importante destacar que la relación entre el IMC y las HL en niños es multidimensional, es compleja y está influenciada por diversos factores, incluidos los aspectos genéticos, ambientales y sociales (He et al, 2024). A pesar de ello, en este estudio se verificó que los niños que presentan un elevado IMC (exceso de peso) versus los que tienen IMC normal han mostrado un pobre rendimiento en la HL.…”
Section: Discussionunclassified
“…The underlying mechanisms that might explain our observed association between motor skills and ADI are likely multifaceted, encompassing environmental, psychological, and physiological elements ( 44 ). Socioeconomic disadvantage is often synonymous with increased environmental pollutants, reduced access to physical activity facilities, and elevated stress levels, all of which could potentially impair motor skill acquisition, cognition and maintenance.…”
Section: Discussionmentioning
confidence: 99%